1993
DOI: 10.1111/j.1476-5381.1993.tb13444.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A1‐receptor stimulated increases in intracellular calcium in the smooth muscle cell line, DDT1MF‐2

Abstract: 1 The effect of a range of adenosine receptor agonists on intracellular free calcium concentration ([Ca2+]j) has been studied in the hamster vas deferens smooth muscle cell line DDTMF-2.2 Adenosine receptor agonists elicited a rapid and maintained increase in [Ca2+], in fura-2 loaded DDTIMF-2 cells. The initial rise could be maintained in the absence of extracellular calcium, whereas the maintained or plateau phase was dependent upon the presence of extracellular calcium and appeared to be associated with calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 35 publications
3
24
0
Order By: Relevance
“…Like others (El-Etr et al, 1992;Dickenson and Hill, 1993;Akbar et al, 1994;Freund et al, 1994), we found that PTX completely abolished A 1 receptor potentiation of PLC activity, confirming an active role of G i /o -proteins in this process. There is no evidence that ␣ subunits of G i /o -proteins have any effects on PLC (Neer, 1995), but it is widely accepted that ␤␥ subunits are the signal transducers for the PTX-sensitive PLC stimulation mediated by G i /o -proteins (Zhu and Birnbaumer, 1996).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Like others (El-Etr et al, 1992;Dickenson and Hill, 1993;Akbar et al, 1994;Freund et al, 1994), we found that PTX completely abolished A 1 receptor potentiation of PLC activity, confirming an active role of G i /o -proteins in this process. There is no evidence that ␣ subunits of G i /o -proteins have any effects on PLC (Neer, 1995), but it is widely accepted that ␤␥ subunits are the signal transducers for the PTX-sensitive PLC stimulation mediated by G i /o -proteins (Zhu and Birnbaumer, 1996).…”
Section: Discussionsupporting
confidence: 90%
“…Very often the coupling of adenosine A 1 receptors to PLC␤ is synergistic, with the stimulation evoked by other receptors like ␣ 1 adrenergic receptors (El-Etr et al, 1989;Biber et al, 1996), histamine H 1 receptors (Dickenson and Hill, 1993), muscarinic receptors (Biden and Browne, 1993), or thyrotropin receptors (Okajima et al, 1995). There are, however, also reports suggesting direct activation of PLC by adenosine A 1 receptors (Gerwins and Fredholm, 1992b;Freund et al, 1994).…”
Section: Abstract: Inhibitory G-protein; ␤␥ Subunits; Inositol Phospmentioning
confidence: 99%
“…However, the pKb for methiothepin obtained in this study is about 1 order of magnitude higher than its affinity for rat and mouse 5-HTIB receptors (Boess & Martin, 1994 and OC2-adrenoceptors expressed at high concentrations in transfected CHO cells are able to inhibit adenylyl cyclase (the normal effector system for these receptors) and activate phospholipase C (Felder et al, 1991;Dell'Acqua et al, 1993;Iredale et al, 1994). In DDTIMF-2 cells, activation of the endogenously expressed adenosine Al receptor results in both the inhibition of adenylyl cyclase and the activation of phospholipase C through PTX-sensitive pathways (Ramkumar et al, 1990;White et al, 1992;Dickenson & Hill, 1993). Furthermore, Ramkumar et al (1990) have shown that the endogenous adenosine Al receptor in DDT1MF-2 cells is expressed at high levels (0.8-0.9 pmol mg-' of protein).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore of the five PKC isozymes expressed in H9c2 cells (PKC-, PKC-β1, PKC-, PKC-, and PKC-ζ) adenosine stimulates the nuclear translation of PKC- [50]. Since DAG activates PKC- and PKC-, it is conceivable that the Gi/o-protein coupled A1 adenosine receptor promotes PKC-/ activation via G-protein β subunit-mediated stimulation of phospholipase C [42,43,46]. It would be of interest in future studies to determine the PKC isozyme(s) involved in A1 adenosine receptorinduced TG2 activation.…”
Section: Role Of Protein Kinases In A1 Adenosine Receptor-mediated Tgmentioning
confidence: 99%